Is it time to include legumes in plant silicon research?. (10th April 2020) - Putra, Rocky; Powell, Jeff R.; Hartley, Susan E.; Johnson, Scott N.
Abstract: To date, the functional role of plant silicon has mostly been investigated in grasses (Poaceae). This potentially overlooks the importance of silicon in other plant functional groups such as legumes (Fabaceae). Legumes form a symbiotic relationship with nitrogen‐fixing bacteria (rhizobia) inside the root nodules for fixing atmospheric nitrogen. A small, but growing number of studies suggest that silicon promotes this symbiotic relationship. We consider how legumes may take up and deposit silicon relative to what is known about these processes in grasses. We synthesize information about how silicon affects legume growth and function in the context of environmental stresses and the legume–rhizobia symbiosis. The available literature indicates that silicon is broadly beneficial to legumes, alleviating the effects of stresses including metal toxicity, salinity, alkalinity and pathogens. Crucially, there is also evidence that silicon promotes the legume–rhizobia interaction including increased root nodulation, numbers of bacteroids and nitrogen fixation across several legume species. We propose a model for how silicon may benefit the legume–rhizobia interaction. We hypothesize that silicification in the tissues may reduce the high metabolic cost of carbon‐based compounds in cell wall construction, optimize solute transport and gas exchange in root nodules and/or promote protection against environmental stresses. We therefore propose a hypothetical framework to better understanding the impacts of silicon on legume–rhizobia relationships. We also suggest potential research priorities that would help us to better understand the functional role of silicon in nitrogen‐fixing legumes. These research priorities focus on characterizing how silicon affects the chemical dialogues between the host plant and its rhizobial partner, how silicon is deposited in legume roots and how resources are exchanged by the two. Given the growing importance of legumes at a global scale, silicon could play a vital role in improving legume health and productivity with manifold environmental benefits. A free Plain Language Summary can be found within the Supporting Information of this article. Abstract : A free Plain Language Summary can be found within the Supporting Information of this article